Taste priming shapes online moral judgment: implications for cyberspace governance - Huang, Xianchao; Zang, Shiying; Wang, Jingxuan; Zheng, Yifan; Bai, Zhuolan; Huang, Jinfeng (Frontiers in Psychology, 2025)
This study explores the link between taste perception and moral judgment, focusing on how tastelessness and varying taste intensities influence the assessment of online events. Participants were exposed to taste priming, ranging from tastelessness to mild and intense sweetness, as well as mild and intense bitterness, to evaluate their moral judgments on events with varying degrees of morality. The findings revealed no significant difference between the tasteless and sweet priming groups. However, the bitterness group exhibited complex effects: moderate bitterness led to the harshest judgments of obvious immoral events, while intense bitterness resulted in stricter judgments for moral events and more lenient judgments for immoral ones. These results suggest that tastelessness may mimic the effects of sweetness, and the influence of bitterness varies with its intensity. The study offers a new perspective on cyberspace governance, suggesting that regulating taste-related stimuli could influence online moral judgment and decision-making processes.